Sobre os tipos de Lepidoptera depositados em museus brasileiros. XXV: Nymphalidae (Charaxinae) descrito por Mário Rosa (suplemento); Zygaenidae por A.M. da Costa Lima; Saturniidae (Hemileucinae) por A. Mabilde (suplemento), Castniidae por L. Pfeiffer e Arctiidae (Pericopinae) por Oscar Monte - Mielke,Olaf H.H. (1999)
A list of Nymphalidae (Charaxinae) described by Mário Rosa (supplement); Zygaenidae by A. M. da Costa Lima, Saturniidae (Hemileucinae) by A. Mabilde (supplement), Castniidae by L. Pfeiffer, and Arctiidae (Pericopinae) by O. Monte, with repositories of their types are presented. Lectotypes are designated for Dirphia glauca Mabilde, 1986 and Casínia pellonia catenigra Pfeiffer, 1917.